Director overseas experience and cross-border acquisitions: Evidence from China - LIU Chenxi (Institutional Knowledge at Singapore Management University, 2025)
This study investigates the impact of director overseas experience on firms’ cross-border acquisition decisions. We find that firms with directors who have overseas experience tend to engage in more cross-border acquisitions. This finding remains robust across various types of overseas experience. This correlation is unlikely to be influenced by omitted variable biases or driven by reverse causality, where firms deliberately employ directors with overseas experience before initiating cross-border acquisitions. Additionally, director overseas experience is associated with higher announcement returns and enhanced post-merger performance. Further analysis reveals that director overseas experience affects cross-border acquisition decisions primarily through the cultural inclusivity channel. These results suggest that director overseas experience plays a significant role in facilitating value-enhancing cross-border acquisitions.